Le profilage dans le cadre d'une procédure d'embauche entre particuliers Une analyse du cadre légal suisse avec un accent sur la portée du droit fondamental à l'autodétermination en matière informationnelle - Christ, Myriam (sui generis Verlag, 2023)
The new data protection law now contains a legal definition of profiling. The question of the extent to which profiling is legal as part of a recruitment process that is subject to Swiss private law has not yet been addressed in teaching. This post was written with the aim of closing this gap. Several questions are clarified: Is the use of profiling as part of such a recruitment process legal? What possible limits are there for the employer? Are the applicable regulations compatible with higher law, in particular with the Federal Constitution, the ECHR and European constitutional law? What legal measures could be implemented to ensure better protection of candidates' rights?